Literature Review MULTI-FACTORIAL INFLUENCES ON MALARIA TRANSMISSION DYNAMICS IN INDONESIA: INSIGHTS FROM CLIMATE TO COMMUNITY INTERVENTIONS - Ghozi, Muhammad Ali; Rejeki, Dwi Sarwani Sri; Wijayanti, Siwi Pramatama Mars (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Indonesia is a tropical climate country with one of its characteristics having high rainfall and lasting relatively long. High rainfall levels cause waterlogging which has the potential to increase the number of mosquito populations. The purpose of this literature review is to determine the effect of weather conditions, namely rainfall and air temperature on the possibility of a malaria outbreak. The method used is to review selected articles with a search engine via Google Scholar, PubMed, and ScienceDirect by entering the keywords rainfall, climate and malaria. The search process to exclude articles used for this literature review uses the PRISMA method. And the results of the literature review show 11 articles discussing weather conditions that affect mosquito populations in Indonesia (Yogyakarta, Bengkulu and Ambon), India, Nigeria, Ethiopia, Mali, Uganda and South Africa. Research in Bengkulu City and Ambon City found a negative correlation between rainfall and temperature on malaria infections. In Limpopo Province, South Africa, data shows the seasonal dynamics of the role of rainfall identified where the December to February rainy season plays a major role in influencing malaria cases in the following year. In Oyam district, Uganda, a malaria outbreak was facilitated by aquatic habitats of Anopheles near houses created by human activities, following increased rainfall.